The p53/miRNAs/Ccna2 pathway serves as a novel regulator of cellular senescence: Complement of the canonical p53/p21 pathway. Issue 3 (7th March 2019) - Xu, Shun; Wu, Weijia; Huang, Haijiao; Huang, Ruxiao; Xie, Luoyijun; Su, Ailing; Liu, Shuang; Zheng, Ruinian; Yuan, Yuan; Zheng, Hui‐ling; Sun, Xuerong; Xiong, Xing‐dong; et al.
Abstract: Aging is a multifactorial process characterized by the progressive deterioration of physiological functions. Among the multiple molecular mechanisms, microRNAs (miRNAs) have increasingly been implicated in the regulation of Aging process. However, the contribution of miRNAs to physiological Aging and the underlying mechanisms remain elusive. We herein performed high‐throughput analysis using miRNA and mRNA microarray in the physiological Aging mouse, attempted to deepen into the understanding of the effects of miRNAs on Aging process at the "network" level. The data showed that various p53 responsive miRNAs, including miR‐124, miR‐34a and miR‐29a/b/c, were up‐regulated in Aging mouse compared with that in Young mouse. Further investigation unraveled that similar as miR‐34a and miR‐29, miR‐124 significantly promoted cellular senescence. As expected, mRNA microarray and gene co‐expression network analysis unveiled that the most down‐regulated mRNAs were enriched in the regulatory pathways of cell proliferation. Fascinatingly, among these down‐regulated mRNAs, Ccna2 stood out as a common target of several p53 responsive miRNAs (miR‐124 and miR‐29), which functioned as the antagonist of p21 in cell cycle regulation. Silencing of Ccna2 remarkably triggered the cellular senescence, while Ccna2 overexpression delayed cellular senescence and significantly reversed the senescence‐induction effect of miR‐124 and miR‐29. Moreover, these p53 responsive miRNAs were significantly up‐regulated during the senescence process of p21‐deficient cells; overexpression of p53 responsive miRNAs or knockdown of Ccna2 evidently accelerated the cellular senescence in the absence of p21. Taken together, our data suggested that the p53/miRNAs/Ccna2 pathway might serve as a novel senescence modulator independent of p53/p21 pathway.